2017
DOI: 10.1111/mec.14177
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional landscape of seasonal coat colour moult in the snowshoe hare

Abstract: Seasonal coat colour change is an important adaptation to seasonally changing environments but the evolution of this and other circannual traits remains poorly understood. In this study, we use gene expression to understand seasonal coat colour moulting in wild snowshoe hares (Lepus americanus). We used hair colour to follow the progression of the moult, simultaneously sampling skin from three moulting stages in hares collected during the peak of the spring moult from white winter to brown summer pelage. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 103 publications
4
57
0
Order By: Relevance
“…The 3‐individuals’ dataset provided higher power (0.82 vs. 0.72 to detect a 1.5‐fold change for a probability of false positives of 0.05) and lower BCV (0.16 vs. 0.21) when compared to the 4‐individuals’ dataset. This estimated power is comparable to that of the snowshoe hare dataset from Ferreira et al, () (0.85 to detect 1.5‐fold changes in expression), and adequate to detect differential expression for lowly expressed genes (Todd, Black, & Gemmell, ). Therefore, hereafter we report the results from the analyses of the 3‐individuals’ dataset.…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…The 3‐individuals’ dataset provided higher power (0.82 vs. 0.72 to detect a 1.5‐fold change for a probability of false positives of 0.05) and lower BCV (0.16 vs. 0.21) when compared to the 4‐individuals’ dataset. This estimated power is comparable to that of the snowshoe hare dataset from Ferreira et al, () (0.85 to detect 1.5‐fold changes in expression), and adequate to detect differential expression for lowly expressed genes (Todd, Black, & Gemmell, ). Therefore, hereafter we report the results from the analyses of the 3‐individuals’ dataset.…”
Section: Resultssupporting
confidence: 62%
“…The inspection of the MDS plot revealed that the skin samples of one individual consistently deviated from the remaining samples and did not capture the individualization of the sampled molt stages aimed with our sampling strategy (Figure ) (Ferreira et al, ). This suggests an artificial bias during sampling that increased the variance in the dataset.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations